UKRAINIAN COURTS IN CRISIS: MAINTAINING THE INTEGRITY OF THE JUDICIAL SYSTEM IN TIMES OF CONFLICT - Nazarko, Artem (Collection of scientific papers «ΛΌГOΣ», 2023)
This article discusses the challenges faced by the Ukrainian judicial system during the ongoing conflict in Ukraine and the efforts being made to maintain its integrity. The author highlights the impact of the conflict on the courts, including the loss of judges and the destruction of court buildings, and examines the measures taken to address these challenges. The article also discusses the reforms that have been implemented to strengthen the independence and impartiality of the judiciary. Finally, the author emphasises the need for continued support for these efforts to ensure the integrity of the Ukrainian judicial system in times of conflict.